2016
DOI: 10.1590/0004-282x20160060
|View full text |Cite
|
Sign up to set email alerts
|

Presence or absence of cognitive complaints in Parkinson’s disease: mood disorder or anosognosia?

Abstract: We intended to evaluate whether non-demented Parkinsons’s disease (PD) patients, with or without subjective cognitive complaint, demonstrate differences between them and in comparison to controls concerning cognitive performance and mood. We evaluated 77 subjects between 30 and 70 years, divided as follows: PD without cognitive complaints (n = 31), PD with cognitive complaints (n = 21) and controls (n = 25). We applied the following tests: SCOPA-Cog, Trail Making Test-B, Phonemic Fluency, Clock Drawing Test, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 24 publications
1
31
0
2
Order By: Relevance
“…Such findings have also been reported in other dementing disorders (Hendrie et al, 1997) as well as in healthy aging (Balash et al, 2013). As suggested in several previous studies (Marino et al, 2009;Sitek et al, 2011;Santangelo et al, 2014;Castro et al, 2016), affective symptoms could worsen the subjective perception of cognitive deficits in PD patients. Another possibility is that facing cognitive difficulties in everyday situations gives rise to depressive symptoms or apathy, but such cognitive problems were not captured by the task battery used in the present study.…”
Section: Associations Between Cognitive Deficits and Psychiatric Sympsupporting
confidence: 82%
“…Such findings have also been reported in other dementing disorders (Hendrie et al, 1997) as well as in healthy aging (Balash et al, 2013). As suggested in several previous studies (Marino et al, 2009;Sitek et al, 2011;Santangelo et al, 2014;Castro et al, 2016), affective symptoms could worsen the subjective perception of cognitive deficits in PD patients. Another possibility is that facing cognitive difficulties in everyday situations gives rise to depressive symptoms or apathy, but such cognitive problems were not captured by the task battery used in the present study.…”
Section: Associations Between Cognitive Deficits and Psychiatric Sympsupporting
confidence: 82%
“…Three studies found an association between subjective complaints and poorer cognitive performances, 5 6 7 whereas others failed to show clear relationship 8 or found that cognitive scores were higher in patients with SCCs than in those without SCCs. 9 …”
Section: Introductionmentioning
confidence: 99%
“…These studies used various methods to define SCCs, with some assessing SCCs using a simple yes/no question, 6 8 9 and others using questionnaires focusing on memory symptoms only. 5 7 However, because the pattern of cognitive impairment in patients with PD is not identical to that of AD, other tools employing questions covering various cognitive symptoms beyond memory complaints are needed.…”
Section: Introductionmentioning
confidence: 99%
“…A significant factors contributing to reporting different SCD are brain diseases of different aetiologies. In comparison to healthy people, an increased SCD is the feature of people with Parkinson disease [19], after head injuries [20,21], with cardiovascular diseases [22], after strokes [23,24], in multiple sclerosis [25,26] and in early stages of Alzheimer disease [27]. Similarly to healthy, in clinic groups the connection between increased SCD and depression, anxiety, feeling of stress was noted [28].…”
Section: Introductionmentioning
confidence: 98%